Mechanism of block by tedisamil of transient outward current in human ventricular subepicardial myocytes - Wettwer, Erich (1998)
1. Tedisamil is a new antiarrhythmic drug with predominant class III action. The aim of the present study was to investigate the blocking pattern of the compound on the transient outward current (I(to)) in human subepicardial myocytes isolated from explanted left ventricles. Using the single electrode whole cell voltage clamp technique, I(to) was analysed after appropriate voltage inactivation of sodium current and block of calcium current. 2. Tedisamil reduced the amplitude of peak I(to), but did not affect the amplitude of non-inactivating outward current. The drug accelerated the apparent rate of I(to) inactivation. The reduction in time constant of I(to) inactivation depended on drug concentration, the apparent IC(50) value was 4.4 μM. 3. Tedisamil affected I(to) amplitude in a use-dependent manner. After 2 min at −80 mV, maximum block of I(to) was reached after 4–5 clamp steps either at the frequency of 0.2 or 2 Hz, indicating that the block was not frequency-dependent in an experimentally relevant range. Recovery from block was very slow and proceeded with a time constant of 12.1±1.8 s. Also in the presence of drug, a fraction of channels recovered from inactivation with a similar time constant as in control myocytes (i.e. 81±40 ms and 51±8 ms, respectively, n.s.). 4. From the onset of fractional block of I(to) by tedisamil during the initial 60 ms of a clamp step, we calculated k(1)=9×10(6) mol(−1) s(−1) for the association rate constant, and k(2)=23 s(−1) for the dissociation rate constant. The resulting apparent K(D) was 2.6 μM and is similar to the IC(50) value. 5. The effects of tedisamil on I(to) could be simulated by assuming a four state channel model where the drug binds to the channel in an open (activated) conformation. It is concluded that in human subepicardial myocytes tedisamil is an open channel blocker of I(to) and that this effect probably contributes to the antiarrhythmic potential of this drug.